Solusi IoT untuk adaptasi New Normal - Adhie Tri Wahyudi; Erni Suparti; Bagus Ismail Adhi Wicaksana (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2020)
Internet of Things (IoT) is a concept that utilizes internet network connectivity for a unified system communication. Analysis conducted on the keyword "Internet of Things" by using Google Trends shows trends up from mid 2013 to 2020. IoT will be a part of human culture which is implemented in all sectors of life. The corona virus pandemic is like a blessing in disguise in terms of the adoption and intervention of technology in all settings of human life. This is because during the Covid-19 pandemic, technology was present to be a solution and provide efficiency. This paper was prepared with the aim of completing a study of the application and adoption of information technology, specifically the field of the Internet of Things (IoT) in adaptation to New Normal life. To achieve the goal, this paper is divided into 3 parts, namely the IoT concept and vision section, the existing IoT implementation section based on the physical setting or place and the IoT solution section for New Normal adaptation after the co-19 pandemic in Indonesia. Based on the analysis and discussion, it can be concluded that experts and government are able to react quickly and appropriately in implementing technology (especially IoT) in Indonesia. However, it is still ineffectiveness and inefficiency, because each government unit’s builds its own system. Next, Indonesian government needs to think about and do is to integrate the system. So, it will be able to produce an integrated information that can be used by all elements of operations in all government unit’s that need it.